Effect of dual-attention task on attack and defensive actions in fencing - Gutierrez-Davila, M.; Rojas, F. J.; Gutierrez-Cruz, C.; Navarro, E. (European Journal of Sport Science, 2017)
The objectives of this study were to investigate the effect that the presence of two stimuli that require two different responses (dual-attention) has both, on offensive reaction-response time to a light stimulus, and on defensive response time when the stimulus is a real fencing attack. Twenty-five elite fencers and a fencing master were included in the study. The equipment included four force plates adapted to a scaffold that served as a fencing piste. Two force plates were placed, at the start position, under the fencer`s feet and another two plates were placed under the master`s feet. The results demonstrate that choice reaction time to visual stimuli increases in dual-task conditions with respect to simple reaction time, whereas the mean horizontal force tends to decrease in dual-task. However, when the stimulus was an opponent`s movement, dual-task conditions did not have any effect on the time required to initiate a defensive action. The changes in reaction time when real movements were used as stimuli challenge the validity of the reaction time to visual stimuli paradigm as a predictor of performance in fencing. Also, the results obtained demonstrate that perceptual and attentional processes play a major role in fencer performance in real competition.